Vitamin D supplementation combined with aerobic physical exercise restores the cell density in hypothalamic nuclei of rats exposed to monosodium glutamate. (December 2022) - Muraro, Eduardo Natan; Sbardelotto, Bruno Marques; Guareschi, Zoé Maria; de Almeida, Wellington; Souza dos Santos, Adriana; Grassiolli, Sabrina; Centenaro, Lígia Aline
Summary: Background & aims: In view of the increase in the prevalence of obesity and metabolic syndrome in childhood and adolescence, this study proposed the early and combined use of treatments to restore brain areas related to satiety. The vitamin D supplementation, aerobic exercise and the combination of these interventions on the structure of arcuate (ARC) and ventromedial (VMH) nuclei of hypothalamus were investigated in monosodium glutamate (MSG)-treated rats. Methods: Wistar rats were separated into five groups: Control group (CT); Obese group injected with MSG (OB); Obese group supplemented with vitamin D (OBvd); Obese group submitted to forced swimming training (OBexe) and Obese group treated with vitamin D supplementation and forced swimming training (OBvd + exe). Results: In the OB group, the visceral fat weight was significantly higher, there was a reduction in the number of glial cells in the ARC nucleus and also in the number of neurons in the ARC and VMH nuclei. Aerobic exercise was able to reduce the visceral fat weight in the OBexe group. The combination of treatments used in the OBvd + exe group reversed the loss of neurons and glial cells produced by MSG in the ARC nucleus. All treated groups exhibited a higher number of neurons in VMH nucleus, but an increase in the glial cells were observed only in the OBexe and OBvd + exe groups. Conclusions: The effectiveness of obesity treatment can be favored through the early and combined use of vitamin D supplementation and aerobic exercise, since these therapies are able to restore brain nuclei involved in the control of food intake.